Optimizing Amine‐Mediated Alkyne–Allene Isomerization to Improve Benzannulation Cascades: Synergy between Theory and Experiments - dos Passos Gomes, Gabriel; Morrison, Alec E.; Dudley, Gregory B.; Alabugin, Igor V. (European journal of organic chemistry, 2019)
A synergy between theory and experiments leads to a milder protocol for base‐mediated high‐temperature benzannulation of alkynylpyridine substrates. Computational analysis identifies mechanistic and energetic nuances in the previously postulated 1,3‐proton transfer isomerization which results in replacement of DBU with a bicyclic guanidine, 1,5,7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD). We have also outlined the general stereoelectronic and geometric hurdles for the design of 1,3‐proton transfer catalysts. Considerable reductions in time, temperature, and equivalents of base underscore the potential of computational analysis to impact experimental design in the laboratory. Catalysts for concerted 1,3‐proton transpositions were engineered using computational analysis and implemented via wet‐lab experimentation. Using this approach, a significantly milder protocol was realized for a DBU‐mediated formal dehydro‐Diels–Alder reaction to produce isoquinolines. Stereoelectronic considerations in catalyst design also provide framework for developing more efficient reagents.